KURIKULUM DAN PEMBELAJARAN PENDIDIKAN DASAR ISLAM MASA TURKI USMANI DAN RELEVANSINYA DI ERA 5.0 - Abdun Nasir, Muhammad Fikri (FIHROS: Jurnal Sejarah dan Budaya, 2024)
In this article, we will discuss the basic education curriculum in the Ottoman era. The education system is the totality of interactions of a set of educational elements that work together in an integrated manner and complement each other towards achieving educational goals that have achieved the common goals of the actors. It is clear that something is expected to be realized after people experience Islamic education as a whole, namely a person's personality that makes him a human being. Muslims experienced a golden peak during the reign of the Abbasids. During that time, famous Islamic thinkers emerged whose thoughts are still discussed and used as a basis. Looking back at the history of Ottoman Turkey, the state of education in Turkey at that time played a very important role in the development of a nation. Most Ottoman rulers tended to be taqlid and fanatical towards one school of thought and opposed other schools of thought. The teaching system developed in Ottoman Turkey was to memorize matan-matan even though students did not understand the meaning, such as memorizing Matan al-Jurumiyah, Matan Taqrib, Matan Alfiah, Matan Sultan, and others. After students memorize the matan, they learn the sharah. Because of this, the lessons became heavier and more difficult for him to memorize. This in turn makes learning more of a textual study rather than an effort to understand and encourages memorization rather than actual understanding. In the history of Muslims, Turkey has a very important role, especially in. The method used in this writing is descriptive qualitative, the author reveals historical facts that occurred during the Ottoman era, through literature review.